2008
DOI: 10.1007/s00005-008-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Ras pathway activation in gliomas: a strategic target for intranasal administration of perillyl alcohol

Abstract: Introduction: Targeted therapy directed at specific molecular alterations is already creating a shift in the treatment of cancer patients. Malignant gliomas commonly overexpress the oncogenes EGFR and PDGFR and contain mutations and deletions of the tumor suppressor genes PTEN and TP53. Some of these alterations lead to activation of the P13K/Akt and Ras/MAPK pathways, which provide targets for therapy. Perillyl alcohol (POH), the isoprenoid of greatest clinical interest, was initially considered to inhibit fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…POH treatment significantly suppressed the Ras/Raf/ERK pathway (4,24). POH also increased Bak and reduced Bcl-xL in different tumors (2,4,25).…”
Section: Discussionmentioning
confidence: 96%
“…POH treatment significantly suppressed the Ras/Raf/ERK pathway (4,24). POH also increased Bak and reduced Bcl-xL in different tumors (2,4,25).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, GSTs show substantial variations in frequencies between ethnic groups and different geographical environmental exposures (Di Pietro et al, 2010), which may explain the divergent results in Brazilians, who form an ethnically heterogeneous population (Carvalho-Silva et al, 2001). It was therefore important to assess polymorphisms in the phase I detoxification enzymes responsible for glutathione conjugation of alkylators and scavenging of free radicals in a population of patients with malignant glioma enrolled in a Phase I/II clinical trial of POH and who had failed multimodal therapy including surgery, radiation, and chemotherapy (da Fonseca et al, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…Perillyl alcohol (POH), a dietary monoterpene found in a variety of plants, suppresses post-translational isoprenylation of the Ras small GTPase superfamily of proteins that stimulate tumor-associated angiogenesis and NFkB signaling (Holstein and Hohl, 2003;da Fonseca et al, 2008a;Chaudhary et al, 2009). This study compared the genotypic profile of GSTM1 and GSTT1 in a group of Brazilian patients with malignant glioma and a control group of healthy individuals living in the same geographical region.…”
Section: Introductionmentioning
confidence: 99%
“…The i.n. technique was also used in a phase I/II clinical trial to administer perillyl alcohol, a Ras inhibitor, and results suggested some antitumor activity without any toxicity in GBM patients (da Fonseca et al, 2008). These studies, together with other pre-clinical reports (Sakane et al, 1999;Thorne et al, 2004;Wang D. et al, 2006;Wang F. et al, 2003), suggest that the i.n.…”
Section: Bypassing the Blood-brain Barriermentioning
confidence: 94%